Understanding cross-cultural variations in organic food purchasing within retail context: a motivations-barriers framework - Hussin, Harniyati; Nasni Naseri, Roszi Naszariah; Shariff, Sharina; Abdul Rashid, Intan Maizura (Faculty of Art and Design, 2025)
The global organic food market has expanded rapidly, surpassing USD 200 billion in 2023, yet adoption rates remain uneven across cultural contexts. While consumer motivations such as health consciousness, environmental concern, and ethical values drive demand, barriers including price sensitivity and skepticism toward certification continue to inhibit widespread adoption. Existing studies often examine these drivers in isolation or within single-country settings, limiting cross-cultural generalizability. This conceptual paper develops the Culture-Motivation-Barrier (CMB) framework, integrating Hofstede’s cultural dimensions with the Theory of Planned Behaviour to explain how cultural values moderate the salience of motivations and barriers in shaping organic food purchasing. The framework highlights how individualism and collectivism, uncertainty avoidance, and long-term orientation influence consumer decision pathways, while also acknowledging the role of economic moderators such as price sensitivity. From a retailing perspective, the framework underscores the importance of tailoring product labelling, in-store communication, and certification strategies to align with cultural expectations. Theoretically, this work bridges cultural psychology and sustainable consumption, advancing understanding of cross-national differences in consumer behavior. Practically, it offers actionable insights for marketers, retailers, and policymakers to design culturally responsive strategies that foster sustainable food consumption and contribute to global sustainability goals.